On the lower operation limit and the gain of flexibility of an innovative segmented tray column - Fasel, Henrik; Grünewald, Marcus; Riese, Julia (Journal of Advanced Manufacturing and Processing)
Abstract Operating windows of conventional tray columns may not be large enough to ensure a sufficient separation with the current or future challenges of a volatile energy and raw material supply. Therefore, an innovative, segmented separation tray has been developed, which enlarges the operation window and thus leads to a higher flexibility, managing the challenges of higher volatility in downstream processes. In this contribution, a hydrodynamic characterization and the resulting lower operation limits of this segmented tray are presented. Furthermore, an approach to obtain shorter start‐up times for the column and a resulting faster response time to changes in the process are presented. The feasibility of this type of operation is evaluated by the investigation of the stability of the tray under new operation conditions.
Keywords: General Medicine

A systematic approach to define flexibility in chemical engineering - Bruns, Bastian; Herrmann, Felix; Polyakova, Maria; Grünewald, Marcus; Riese, Julia (Journal of Advanced Manufacturing and Processing)
Abstract Increasing economic and environmental challenges leads to the need for changes in the chemical industry. In this context, a promising approach is utilizing flexible apparatuses and flexible plants to react to changing boundary conditions. However, the concept of flexibility in chemical engineering, which originated in manufacturing, still lacks a comprehensive organization and categorization of different types of flexibility. Thus, in this work, the origin of flexibility in manufacturing is traced, and a literature overview on flexibility in chemical engineering is provided. Based on a subsequent cluster analysis, four types of flexibility are identified and defined. Furthermore, this work enables research on flexibility to be integrated into a general and consistent definition of flexibility. The definitions are applied to examples from literature to achieve comparability. While enabling the qualitative assessment of flexibility, this work identifies open research gaps regarding the quantification of flexibility.
Keywords: General Medicine